Identification of parasitic infection in laboratory rodents through contrast management methods - Raslan, Nurul Ain Fatin (2021)
Parasites may be found in the skin and intestine of the laboratory mice (Mus musculus) and rat (Rattus norvegicus). High parasitic burden are known to influence experimental outcomes and results. Therefore, it is important to determine the impact of parasitic infestations on rodent study, especially in Malaysia where some rodent colonies are still being kept in conventional systems. This study allows for the identification of common parasitic infection of laboratory rodents, assess the parasitic infection based on management methods of stocking density and environmental condition, and compare the parasitic infection between two conventional animal facilities. Firstly, seventytwo (72) laboratory rodents of BALB/c, ICR and Sprague Dawley (SD) were chosen from an animal facility located in Klang Valley and subjected to identification of common parasitic infections. Secondly, one hundred and eight (108) male BALB/c mice were randomly chosen and placed in three groups to reflect different stocking densities of 3, 6 and 9 mice per group, under different environmental settings of regulated and non-regulated environment for 5 weeks. Thirdly, sixty (60) BALB/c mice and sixty (60) SD rats were chosen to compare the parasitic infection between two conventional animal facilities. Helminths, ectoparasites and blood parasites were examined using conventional techniques. Parasites were identified based on observation and classification of their distinct characteristics under a compound microscope. Results showed that mice were commonly infected with pinworms; Syphacia obvelata (S. obvelata) and Aspiculuris tetraptera (A. tetraptera) whereas, rats were infected with Syphacia muris (S. muris) and A. tetraptera. The prevalence of the pinworms; S. obvelata in the mice range from 20.83% to 41.67%, S. muris in the rats at 83.33%, and A. tetraptera range from 8.33% to 45.83% in both species. Although the second findings revealed BALB/c mice placed in two different management settings had no association between parasitic infections with various stocking density and between different environmental condition using repeated-measures ANOVA, but association was observed using gastrointestinal examination and tape impression test when using one-way ANOVA. Ectoparasites suspected to be immature mites detected in non-regulated environment at a prevalence of 20.4%, with an association found using the tape impression test under one-way ANOVA. Finally, the comparison between two different conventional animal facilities demonstrated that ICR mice were infected with a common fur mite; Myocoptes musculinus (M. musculinus) and lice; Polyplax serrata (P. serrata) while the SD rats were infected by uncommon parasites; Heterakis spumosa (H. spumosa) that is normally found in wild rats, and Chirodiscoides caviae (C. caviae), a common fur mite in guinea pigs. The results also revealed an association between parasitic infections and different management of animal facilities for laboratory mice and rats using the Chi-square test. Overall, management plays an important factor in parasitic infestation of laboratory rodents. The findings highlight the parasites identified in laboratory rodents varied according to the parasitological methods used following the contrast management method of stocking density, environmental condition and facility.